Influence of sex, age, slaughter mass and source farm on carcass composition of fattening dairy cattle - Phonkhokkong, P.; Tuntivisoottikul, K. (My University, 2020)
Sex significantly influenced total tendons mass and percentage of tendons mass (P<0.01). The factor had also significantly affected to total mass, total lean meat mass and total bone mass (P<0.05). Age influenced total bone mass, total fat mass, percentage of bone and muscle:fat ratio (P<0.05) and proportion of fat (P<0.01). Chilled carcass mass, total mass of lean meat, bone, fat, and tendons were highly significantly affected by slaughter mass (P<0.01), which also significantly influenced percentage of fat (P<0.05). Cattle with a slaughter mass more than 650 kg had higher averages of chilled carcass mass, total lean meat, bone, fat, and tendon mass and percentage of fat than lighter animals. The factor of source farm significantly effected chilled carcass mass and total fat mass (P<0.01), as well as total mass of lean meat and bone and percentages of bone and of fat (P<0.05).
Keywords: Carcass Composition; Fattening Dairy Cattle; Thailand